Study of gamma-ray emission by proton beam interaction with injected Boron atoms for future medical imaging applications. (13th March 2017) - Petringa, G.; Cirrone, G.A.P.; Caliri, C.; Cuttone, G.; Giuffrida, L.; Larosa, G.; Manna, R.; Manti, L.; Marchese, V.; Marchetta, C.; Margarone, D.; Milluzzo, G.; et al.
Abstract: In this work an experimental and theoretical study of gamma-prompt emission has been carried out with the main aim being to understand to what extent this approach can be used during a treatment based on proton-boron fusion therapy. An experimental campaign, carried out with a high purity Germanium detector, has been performed to evaluate the gamma emission from two pure 11 B and 10 B targets. Furthermore, a set of analytical simulations, using the Talys nuclear reaction code has been performed and the calculated spectra compared with the experimental results. These comparisons allowed us to successfully validate Talys which was then used to estimate the gamma emission when a realistic Boron concentration was considered. Both simulations and experimental results suggest that the gamma emission is low at certain proton energies, thus in order to improve the imaging capabilities, while still maintaining the Boron therapeutic role, we propose the addition of natural Copper bound by a dipyrromethene, BodiPy, to boron atoms. Analytical simulations with Talys suggest that the characteristic spectrum of the copper prompt gamma-rays has several peaks in the energetic regions where the background is negligible.